Atopy in chronic urticaria: an important yet overlooked issue - Chen, Qiquan; Yang, Xianjie; Ni, Bing; Song, Zhiqiang (Frontiers in Immunology, 2024)
Chronic urticaria (CU) is one of the most common dermatological diseases and has a significant impact on the quality of life of patients. However, the pathogenesis of this disease remains unclear. Autoimmunity in chronic spontaneous urticaria (CSU) has received considerable attention and has been studied previously. Atopy is an important characteristic of CU; however, it has not been fully recognized. Atopy predisposes individuals to immune responses to allergens, leading to type 2 inflammation and immunoglobulin E (IgE) overproduction. Compared with healthy individuals, patients with CU have a higher proportion of atopy, and an atopic background is correlated with the clinical characteristics of CU. The total IgE levels in patients with CU is significantly higher than those in healthy individuals. Although its level is not higher than that in classic allergic diseases, it is closely related to CU. Exogenous allergens, auto-allergens, and specific IgEs, which are closely related to atopy, have been reported, and their roles in CU pathogenesis are also being studied. Local and systemic atopic inflammation is present in patients with CU. This review summarizes the current knowledge regarding atopy and CU, speculating that there are CU subtypes, such as atopic CSU or atopic chronic inducible urticaria (CIndU) and that atopy may be involved in the pathogenesis of CU. These findings provide a new perspective for a comprehensive understanding of the clinical features of CU and further research regarding its pathogenesis.